Transforming Energy and Resource Management with AI: From Theory to Sustainable Practice - Zaharuddin; Sipah Audiah; Yulia Putri Ayu Sanjaya; Ora Pertiwi Daeli; Michael Johnson (Pandawan Sejahtera Indonesia, 2024)
Efficient and sustainable energy management is crucial for addressing global environmental challenges. Artificial intelligence (AI) has emerged as a significant tool in the energy revolution, enhancing operational efficiency and integrating renewable energy sources. This study examines the impact of AI on optimizing energy and resource management, focusing on increasing renewable energy use and efficiency. Using a quantitative and exploratory approach, data from 100 energy companies that have implemented AI solutions were analyzed. The findings show that AI can improve energy efficiency by 25%, strengthen sustainable operations, and reduce environmental impact. These results align with Complex Systems Theory, highlighting that advanced technologies like AI enhance system adaptability and efficiency. Despite these insights, the study is limited to companies that have adopted AI and focuses solely on the energy sector. This highlights the need for broader research across various sectors and geographic contexts. The implications suggest that AI not only improves energy management but also supports global sustainability efforts, making it vital for a sustainable energy future.